Spatial-Temporal Movements of Free Ranging Pigs at the Wildlife-Livestock Interface of Murchison Falls National Park, Uganda: Potential of Disease Control at a Local Scale - Payne, Ariane; Ogweng, Peter; Ståhl, Karl; Masembe, Charles; Jori, Ferran (Frontiers in Veterinary Science, 2021)
In many Ugandan rural communities, pigs are generally kept under traditional smallholder systems without basic biosecurity measures in place. In some instances, these systems are at the livestock-wildlife interface, as is the case in Nwoya district, which is bordered by Murchison Falls National Park (MFNP). This pig system has potential for the maintenance and transmission of pathogens like African swine fever (ASF) between different herds, and also with wild pigs (warthogs and bushpigs). In this paper, we describe the spatial and temporal pattern of the movements of free ranging domestic pigs in a rural setting in Northern Uganda where ASF is endemic. We also determine their use of habitat to highlight the potential interaction hotspots between domestic pigs and between domestic and wild pig populations. We fitted 10 free-ranging domestic pigs owned by different homesteads with GPS harnesses during rainy and dry seasons. The pig home range, daily distance, activity pattern and habitat use were calculated. Our results show that the maximum area covered (MCP 100%) by the pigs varied between 35,965 and 475,077 m2. The core area varied from 1,317 to 50,769 m2.The pigs’ home ranges were significantly bigger during the dry season than during the rainy season (Wilcoxon test, W= 22, p=0.04). The mean full day (24 hrs) distance was longer in the dry season than in the rainy season (Student test, t=2.7, p=0.03). The pigs were mostly located within their own homestead, but they also used other homesteads, grass and crop fields. This study highlights that free-ranging domestic pigs may cover a wide area, especially during the dry season. Interestingly, the home range of pigs from different herds may overlap with areas used by wild pigs which share crops and other resources in this area. This study provides insights into a better understanding of the potential for spread of diseases such as ASF at small-scale and can be used to raise awareness of such risks and to better target implementation of preventive measures.